Effectiveness of Warm Water Compress With Lemon Aromatherapy and Lavender Aromatherapy Against Primary Dysmenorrhea Pain Levels - Djumi Widarti; ribkha itha; Arum Lusiana (Poltekkes Kemenkes Semarang, 2021)
Background: Primary dysmenorrhea is menstrual pain that occurs since menarche without the presence of pathology in the pelvis that causes disruption of daily activities and decreases the quality of life. Improved blood circulation and aromatic odors can reduce pain. in this study to find out the effectiveness of warm water compresses and lemon aromatherapy with lavender aromatherapy against the level of primary dysmenorrhea pain in young women.Methods: Pre-Experiment with One Group Pre - Post-test design approach. The sampling technique of this study is accidental Sampling. The subjects of this study were 37 young women who suffered from dysmenorrhea and met the criteria. Data analysis using the Wilcoxon test and the Whitney Mann test.Result: research shows Sig Value. (2-tailed) = 0.001. Then the value of Sig. (2-tailed) 0.05 (0.00 0.05) then Ho is rejected and Ha is accepted which can mean that warm water compress and lemon aromatherapy with warm water compress and lavender aromatherapy are effective against decreased dysmenorrhea pain.Conclusion: From the results of the study can be concluded warm water compress and aromatherapy lemon is more effective to reduce dysmenorrhea pain in young women